Ексергетичний аналіз утилізатора теплоти відпрацьованих газів двигунів внутрішнього згоряння когенераційних установок - Горобець, В. Г.; Богдан, Ю. О. (Energy and Automation, 2017)
EXERGY ANALYSIS OF HEAT UTIZATORS OF WASTE HEATED GASES FOR INTERNAL COMBUSTION ENGINES COGENERATION PLANTS V. Gorobets, Ju. Bogdan  Cogeneration plants have a wide range of applications in various industries, in the municipal power industry, in the agro-industrial complex. For example, in agriculture, cogeneration plants are used as a component of biogas plants to provide electric and thermal energy for farms, for the energy supply of greenhouses, poultry, pig farms and cattle farms, etc. The advantages of cogeneration plants are their high efficiency, which is 90-95%, the absence of the need for laying electric and thermal networks, a wide range of variation of the required electrical and thermal power, a short payback period and other factors.In the development of cogeneration plants, one of the most important indicators of efficiency in their operation is the assessment of energy losses when converting heat generated by combustion of fuels in internal combustion engines and gas turbine plants, into mechanical (electrical) and thermal energy, which is subsequently used for the operation of various objects - household and industrial buildings, farms, greenhouses, etc.One of the most informative methods for estimating these losses is the exergy analysis, which makes it possible to determine the thermal, mechanical, electrical, hydraulic and other losses in comparison with the classical thermodynamic analysis of heat flows, which does not take into account certain types of losses, such as hydraulic losses. The method of calculation is developed, the analysis and calculation of exergy losses in the heat utilizer of waste gas of internal combustion engines of cogeneration plants is developed.The purpose of the work is to develop a calculation method, an exergy analysis and estimation of exergic losses in the heat exchange equipment of cogeneration plants.In calculating the exergent efficiency of heat utilizers, the following factors have to be taken into account:1. With a significant cooling of waste gas, the temperature pressure decreases, which leads to an increase in the heating surface of the utilization device, which, in turn, increases the gas-dynamic resistance of the outlet.2. The level of reduction of the cooling temperature of waste gas is limited by the threshold at which condensation of water vapor, containing components of sulfuric acid, which cause corrosion of the outlet pipeline, occurs.3. Losses due to the irreversibility of the heat transfer process.4. Hydraulic and gas-dynamic losses.5. Losses from heat exchange to the environment.6. Loss due to heat conduction along the heat exchangers (taking into account the non-isothermal of the surfaces).In the paper the method of calculation was developed, the analysis of exergic losses was carried out and the exergic efficiency of the new design of heat utilizer of the exhaust gases of the internal combustion engine of the cogeneration plants was determined, which allows to estimate the efficiency of the use of the energy potential of the combustion products taking into account all types of losses. The ways of increasing exergic efficiency of heat utilizers and improvement of ecological characteristics of cogeneration plants are shown.